A student's guide to methodology justifying enquiry - Clough, Peter (Sage Publications, 2007)
Pt. I. Research is Methodology -- 1. What is research? -- 2. What is methodology? -- Pt. II. The Pervasive Nature of Methodology -- 3. Looking: seeing beyond the known -- 4. Listening: issues of voice -- 5. Reading: purpose and positionality -- 6. Questioning: the focus of research -- Pt. III. Making Research Public -- 7. Research design: shaping the study -- 8. Reporting research: telling the story -- 9. Research action: next steps -- App. I. Research planning audit -- App. II. Annotated bibliography of research texts.